Effect of climate change on risk and vulnerability of paddy farmer in Chi watershed (Thai) - Kerdsuk, Vichien; Kerdsuk, Wachiraporn (Asia-Pacific Journal of Science and Technology, 2017)
The study of impact of climate change on risk analysis and vulnerability of paddy farmers in Chi river watershed was conducted through household interviews 1,319 households in 3 provinces. The risk assessment analysis was based on multi-criteria by taking sensitivity, exposure and coping capacity to climate impact criteria as frame of analysis under consideration. These criteria used household economic condition, farmerû dependence on their farms production and the coping capacity to climate impact as proxy of each criteria, of each criteria was explained by multiple indicators. In the past decade (1990s), the climate related disaster that drought was impacted to farmers was more than flood. The households of farmers who were impacted from drought, flood and all both disaster were about 77.49, 46.84 and 33.74 respectively. Climate variation was to be lased of rice yield 64.6% of total rice yield. It made a paddy farmer to vulnerability group 76.12%. The risk from a climate change to farmers in Chi watershed, found that in the normal year, 60.27% of paddy farmer was in the medium risk. 30.47% and 9.25% is in low risk and high risk respectively. In the climate variation, paddy farmer fall to low risk, medium risk and high risk were 22.67%, 53.98% and 23.35% especially. It showed that a paddy farmer group was very much changes from low and medium risk to high risk, the high risk group changes from 9.25 to 23.35%. The risk group was agreed with main income of paddy field, in the normal year, crops were a source of main income, especially from rice, about 50.9% of total income in the households. But in the climate variation year, off-farm income was the main income which was about 68.7% of total income. Income from crops was only 25.2%. Also earn a living of paddy farmer in risk group was depend on income from rice and it had impacted to ability of risk management of them.